Transformation of Retailing in Bangladesh: A Holistic Approach - Alam, Md. Jahangir (Journal of Asian Business Strategy, 2019)
Retailing in Bangladesh is changing rapidly in line with the other countries of the world. The study aims to identify the nature of changes in retailing in Bangladesh along with the practicing theory of retail changes and waves of retail development by reviewing the articles and contents, secondary information from the different sources. Tabular forms of data presentation is used, trend analysis and subjective judgements are deployed in analyzing the data to reach the decisions. The changing nature of retailing in Bangladesh has the three dimensions-the rapid rise of supermarkets in the urban and semi urban areas, accelerations of the e-commerce & e-tailing and a start of multichannel retailing. The practicing pattern of retailing in Bangladesh follows the combined theory of retail changes and belongs to the fourth wave of retail development. The study may help innovating new retail model as well as gives insight to the retail institutions, professionals and policy makers to formulate the proper policy for effective growth and management of the sector.